MyAC Service App: Multifactor Authentication using Android Based for Air Conditioner Service Application - Mohd Yusof, Fatin Nadia; Abdullah, Zubaile (Applied Information Technology And Computer Science, 2024)
MyAC Service is an Android-based air conditioner service application that utilizes Multifactor Authentication (MFA) to secure user accounts. MyAC Service is employs complex passwords and One-time Password (OTP) in the login session, including the email address verification. This paper presents a proposed application aimed at addressing the limitations of existing MyAC Service application in functionality as a booking application. The objective of this study is to develop an MyAC Service application efficiently to do a reservation for air conditioner service and secure user’s accounts from data breach. The application is designed using Java programming language, android technology, and prototype model methodology approach. The expected outcome of this project is the development of a capable Air conditioner service application that can functions to make air conditioner service reservation activity and to verifies a user's identity using MFA security method before access to the application.